Assessing the Sensitivity of Dual-Energy Computed Tomography 3-Material Decomposition for the Detection of Gout. Issue 9 (21st September 2022) - Tse, Justin J.; Kondro, Douglas A.; Kuczynski, Michael T.; Pauchard, Yves; Veljkovic, Andrea; Holdsworth, David W.; Frasson, Viviane; Manske, Sarah L.; MacMullan, Paul; Salat, Peter
Abstract : Objectives: The aim of this study was to assess the accuracy and precision of a novel application of 3-material decomposition (3MD) with virtual monochromatic images (VMIs) in the dual-energy computed tomography (DECT) assessment of monosodium urate (MSU) and hydroxyapatite (HA) phantoms compared with a commercial 2-material decomposition (2MD) and dual-thresholding (DT) material decomposition methods. Materials and Methods: Monosodium urate (0.0, 3.4, 13.3, 28.3, and 65.2 mg/dL tubes) and HA (100, 400, and 800 mg/cm 3 tubes) phantoms were DECT scanned individually and together in the presence of the foot and ankle of 15 subjects. The raw data were decomposed with 3MD-VMI, 2MD, and DT to produce MSU-only and HA-only images. Mean values of 10 × 10 × 10–voxel volumes of interest (244 μm 3 ) placed in each MSU and HA phantom well were obtained and compared with their known concentrations and across measurements with subjects' extremities to obtain accuracy and precision measures. A statistical difference was considered significant if P < 0.05. Results: Compared with known phantom standards, 3MD-VMI was accurate for the detection of MSU concentrations as low as 3.4 mg/dL ( P = 0.75). In comparison, 2MD was limited to 13.3 mg/dL ( P = 0.06) and DT was unable to detect MSU concentrations below 65.2 mg/L ( P = 0.16). For the HA phantom, 3MD-VMI and 2MD were accurate for all concentrations including the lowest at 100 mg/cm 3 ( P = 0.63 and P = 0.55, respectively). Dual-thresholding was not useful for the decomposition of HA phantom. Precision was high for both 3MD-VMI and 2MD measurements for both MSU and HA phantoms. Qualitatively, 3MD-VMI MSU-only images demonstrated reduced beam-hardening artifact and voxel misclassification, compared with 2MD and DT. Conclusions: Three-material decomposition-VMI DECT is accurate for quantification of MSU and HA concentrations in phantoms and accurately detects a lower concentration of MSU than either 2MD or DT. For concentration measurements of both MSU and HA phantoms, 3MD-VMI and 2MD have high precision, but DT had limitations. Clinical implementation of 3MD-VMI DECT promises to improve the performance of this imaging modality for diagnosis and treatment monitoring of gout.